Patron Client in Political Corruption in Circles South Sulawesi BUMD ((Regional Owned Enterprises)) - Amin, Rahma; Sulaiman, Herlina; Muin, Indriani (Al-Amwal : Journal of Islamic Economic Law, 2024)
Purpose – The aim of this research is to understand the forms and processes of political corruption within BUMDs based on patron-client relationships in placing people in strategic positions in the company. Method - This research uses secondary data, namely based on the results of the anti-corruption assessment carried out by TI Indonesia. Then carry out a literacy study to draw conclusions and verify. Result - The political corruption nested within BUMDs in South Sulawesi has had an impact on unsatisfactory performance and achievements, where continuous losses have been found, which is the impact of the recruitment system for BUMD directors which is only based on the politics of retaliation in the regional elections. Implication – Transparency International (TI) Indonesia in the period December 2022-January 2023 has carried out a Transparency in Corporate Reporting assessment of 47 companies or Regional Owned Enterprises (BUMD) in 5 Provinces, South Sulawesi (Sulsel) is one of the provinces assessed. The result was that five South Sulawesi BUMDs were categorized as sick and not transparent in terms of management, making them prone to corruption. Through this research, it is hoped that it can be an evaluation of the performance of BUMDs in South Sulawesi related to company management.